Natural History of Cutaneous Human Polyomavirus Infection in Healthy Individuals - Bopp, Luisa; Wieland, Ulrike; Hellmich, Martin; Kreuter, Alexander; Pfister, Herbert; Silling, Steffi (Frontiers in Microbiology, 2021)
Several human polyomaviruses (HPyVs) were recently discovered. Merkel cell polyomavirus (MCPyV) induces Merkel cell carcinoma. HPyV6, HPyV7, and TSPyV have been associated with rare skin lesions in immunosuppressed patients. HPyV9, HPyV10, and STLPyV have not been convincingly associated with any disease. The aim of this prospective study was to evaluate cutaneous prevalence, persistence and viral load of HPyVs in healthy individuals. 870 forehead and hand swabs were collected from 109 volunteers four to six weeks apart (collection period-1). 59 participants were available for follow-up a decade later (collection period-2). HPyV-DNA prevalence and viral loads of MCPyV, HPyV6, HPyV7, TSPyV, HPyV9, HPyV10, and STLPyV were determined by virus-specific real-time PCRs. Risk factors for HPyV prevalence, short- and long-term persistence were explored by logistic regression analyses. Baseline prevalence rates were similar for forehead and hand: MCPyV 67.9/67.0%, HPyV6 31.2/25.7%, HPyV7 13.8/11.0%, HPyV10 11.9/15.6%, STLPyV 7.3/8.3%, TSPyV 0.9/0.9%, HPyV9 0.9/0.9%. Short-term persistence in period-1 was found in 59.6% (MCPyV), 23.9% (HPyV6), 10.1% (HPyV7), 6.4% (HPyV10), 5.5% (STLPyV) and 0% (TSPyV and HPyV9) on the forehead, with similar values for the hand. Long-term persistence for 9-12 years occurred only for MCPyV (forehead/hand 39.0%/44.1% of volunteers), HPyV6 (16.9%/11.9%), and HPyV7 (3.4%/5.1%). Individuals with short-term persistence had significantly higher viral loads at baseline compared to those with transient DNA-positivity (p<0.001 for MCPyV, HPyV6, HPyV7, HPyV10, respectively). This was also true for median viral loads in period-1 of MCPyV, HPyV6 and HPyV7 of volunteers with long-term persistence. Multiplicity (two or more different HPyVs) was a risk factor for prevalence and persistence for most HPyVs. Further risk factors were older age for HPyV6 and male sex for MCPyV on the forehead. Smoking was not a risk factor. In contrast to MCPyV, HPyV6, HPyV7, and rarely STLPyV, polyomaviruses TSPyV, HPyV9, and HPyV10 do not seem to be long-term constituents of the human skin virome of healthy individuals. Furthermore, this study showed that higher viral loads are associated with both short- and long-term persistence of HPyVs on the skin. HPyV multiplicity is a risk factor for prevalence, short-term and/or long-term persistence of MCPyV, HPyV6, HPyV7 and HPyV10.